ANALYSIS OF PERCEIVED QUALITY OF EDUCATION SERVICE - Murwatiningsih, Murwatiningsih (Department of Management, Faculty of Economics, Semarang State University, Indonesia, 2015)
This study aims to determine the descriptive overview of the quality of education services consisting. The location of this research was at the Economics Faculty of Semarang State University, and the object of the study was student at semester VII of the Economics Faculty. The population of this study was 620 students in the academic year of 2014/2015. Proportional cluster ranom sampling technique was utilized to get 186 samples. The method of collecting data using questionnaires, whereas method of data analysis using non-parametric statistics (descriptive percentages).The result shows that the quality of education services, which can be seen from the dimensions of relevance, efficiency, effectiveness, accountability, responsiveness, creativity, productivity, academic abilities, empathy, and appearance, are perceived well by students. However, this result has not optimal yet, especially on the dimensions of relevance, efficiency and effectiveness.